Cadaveric Testing of a Novel Scapholunate Ligament Reconstruction - Kang, Lana; Dy, Christopher J.; Wei, Mike T.; Hearns, Krystle A.; Carlson, Michelle G. (Journal of Wrist Surgery, 2018)
Background Existing scapholunate interosseous ligament (SLIL) reconstruction techniques include fixation spanning the radiocarpal joint, which do not reduce the volar aspect of the scapholunate interval and may limit wrist motion.Questions/Purpose This study tested the ability of an SLIL reconstruction technique that approximates both the volar and dorsal scapholunate intervals, without spanning the radiocarpal joint, to restore static scapholunate relationships.Materials and Methods Scapholunate interval, scapholunate angle, and radiolunate angle were measured in nine human cadaveric specimens with the SLIL intact, sectioned, and reconstructed. Fluoroscopic images were obtained in six wrist positions. The reconstruction was performed by passing tendon graft through bone tunnels from the dorsal surface toward the volar corner of the interosseous surface. After reduction of the scapholunate articulation, the graft was tensioned within the lunate bone tunnel, secured with an interference screw in the scaphoid, and sutured to the dorsal SLIL remnant. Differences among testing states were evaluated using repeated measures ANOVA.Results There was a significant increase in the scapholunate interval in all wrist positions after complete SLIL disruption. Compared with the disrupted state, there was a significant decrease in scapholunate interval in all wrist positions after reconstruction using a tendon graft and interference screw.Conclusion Our SLIL reconstruction technique reconstructs the volar and dorsal ligaments of the scapholunate joint and adequately restores static measures of scapholunate stability. This technique does not tether the radiocarpal joint and aims to optimize volar reduction.Clinical Relevance Our technique offers an alternative option for SLIL reconstruction that successfully restores static scapholunate relationships.
Keywords: scapholunate ligament; reconstruction; SLIL; ligament; wrist